Synthesis, Characterization, and Theoretical Analysis of Schiff Base Graphene Oxide Utilizing DFT Computing : Sintesis, Karakterisasi, dan Analisis Teoritis Grafena Oksida Basis Schiff Menggunakan Komputasi DFT - Ali Abra Naser (Academia Open, 2025)
General Background: Graphene oxide (GO) and its derivatives, such as Schiff base-functionalized graphene oxide (GOTM), have gained significant attention due to their unique properties and potential applications in various fields. Specific Background: The synthesis and characterization of GOTM involve advanced spectroscopic techniques like FT-IR, XRD, Raman, and FESEM, along with computational analysis using Density Functional Theory (DFT). Knowledge Gap: Despite extensive research on GO, the influence of Schiff base functionalization on its chemical and electronic properties remains inadequately explored. Aims: This study aims to synthesize GOTM, characterize its structural and electronic properties, and analyze its stability and reactivity through DFT calculations. Results: The synthesis of GOTM was confirmed through FT-IR, XRD, Raman, EDX, and FESEM, revealing changes in surface morphology and electronic characteristics compared to GO. DFT calculations showed significant differences in reactivity indices and electronic properties between GO and GOTM. Novelty: This study provides a comprehensive analysis of the impact of Schiff base functionalization on GO’s electronic structure, offering new insights into its reactivity and stability. Implications: The findings contribute to the design of advanced materials with tailored electronic properties for applications in energy, sensors, and environmental technologies. Highlights: Nurses are essential in obesity physiotherapy interventions. Knowledge gaps reduce physiotherapy care effectiveness. Training improves nurse-led obesity management. Keywords: Nurses, Physiotherapy, Obesity, Knowledge, Saudi Arabia